2021
DOI: 10.1111/ijac.13872
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic role of C/Zr ratio in the reaction process, combustion behavior, and synthetic product of 70 wt.% (xC–Zr)–30 wt.% Cu

Abstract: The kinetic role of C/Zr ratio in the reaction processes, combustion behaviors, and synthesized products of 70 wt.% (xC–Zr)–30 wt.% Cu was investigated. Results indicated that ZrC particles were produced by the replacement reaction between carbon atoms and Zr–Cu melt. With an increase in C/Zr ratio, more carbon atoms combined with the zirconium atoms in Zr–Cu liquid. As a result, the formation rate of massive ZrC enhanced, which shortened the ignition time of combustion reaction. On the other hand, the quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…6 Zr in BZC30 is relatively higher. This would restrain the dissolution of Zr-rich phases for the limited solubility of ZrCu liquid, 18) as supported by the occurrence of less solidification structure in Fig. 7.…”
Section: Influence Of Cu Content On the Reaction Processmentioning
confidence: 88%
“…6 Zr in BZC30 is relatively higher. This would restrain the dissolution of Zr-rich phases for the limited solubility of ZrCu liquid, 18) as supported by the occurrence of less solidification structure in Fig. 7.…”
Section: Influence Of Cu Content On the Reaction Processmentioning
confidence: 88%
“…The experimental results showed that the C/Zr ratio had a great influence on the synthesis. The control of C/Zr ratio could effectively improve the product synthesis rate and the remanufacturing efficiency of ZrC (Zhang et al, 2021). Qi et al prepared a new Fe based composite coating based on TiC and CeO 2 for high value vulnerable parts of shield machine.…”
Section: Related Workmentioning
confidence: 99%